Emerging intraoral biosensors - Wang, Jianwu (2021)
Biomedical devices that involved continuous and real-time health-care monitoring have drawn much attention in modern medicine, of which skin electronics and implantable devices are widely investigated. Skin electronics are characterized for their non-invasive access to the physiological signals, and implantable devices are superior at the diagnosis and therapy integration. Despite the significant progress achieved, many gaps remain to be explored to provide a more comprehensive overview of human health. As the connecting point of the outer environment and human systems, the oral cavity contains many unique biomarkers that are absent in skin or inner organs, and hence, this could become a promising alternative locus for designing health-care monitoring devices. In this review, we outline the status of the oral cavity during the communication of the environment and human systems and compare the intraoral devices with skin electronics and implantable devices from the biophysical and biochemical aspects. We further summarize the established diagnosis database and technologies that could be adopted to design intraoral biosensors. Finally, the challenges and potential opportunities for intraoral biosensors are discussed. Intraoral biosensors could become an important complement for existing biomedical devices to constitute a more reliable health-care monitoring system.